Liver Glycogen Phosphorylase Deficiency Leads to Profibrogenic Phenotype in a Murine Model of Glycogen Storage Disease Type VI. Issue 11 (24th September 2019) - Wilson, Lane H.; Cho, Jun‐Ho; Estrella, Ana; Smyth, Joan A.; Wu, Rong; Chengsupanimit, Tayoot; Brown, Laurie M.; Weinstein, David A.; Lee, Young Mok
Abstract : Mutations in the liver glycogen phosphorylase ( Pygl ) gene are associated with the diagnosis of glycogen storage disease type VI (GSD‐VI). To understand the pathogenesis of GSD‐VI, we generated a mouse model with Pygl deficiency ( Pygl −/− ). Pygl −/− mice exhibit hepatomegaly, excessive hepatic glycogen accumulation, and low hepatic free glucose along with lower fasting blood glucose levels and elevated blood ketone bodies. Hepatic glycogen accumulation in Pygl −/− mice increases with age. Masson's trichrome and picrosirius red staining revealed minimal to mild collagen deposition in periportal, subcapsular, and/or perisinusoidal areas in the livers of old Pygl −/− mice (>40 weeks). Consistently, immunohistochemical analysis showed the number of cells positive for alpha smooth muscle actin (α‐SMA), a marker of activated hepatic stellate cells, was increased in the livers of old Pygl −/− mice compared with those of age‐matched wild‐type (WT) mice. Furthermore, old Pygl −/− mice had inflammatory infiltrates associated with hepatic vessels in their livers along with up‐regulated hepatic messenger RNA levels of C‐C chemokine ligand 5 ( Ccl5 / Rantes ) and monocyte chemoattractant protein 1 ( Mcp‐1 ), indicating inflammation, while age‐matched WT mice did not. Serum levels of aspartate aminotransferase and alanine aminotransferase were elevated in old Pygl −/− mice, indicating liver damage. Conclusion : Pygl deficiency results in progressive accumulation of hepatic glycogen with age and liver damage, inflammation, and collagen deposition, which can increase the risk of liver fibrosis. Collectively, the Pygl ‐deficient mouse recapitulates clinical features in patients with GSD‐VI and provides a model to elucidate the mechanisms underlying hepatic complications associated with defective glycogen metabolism. Abstract : Pygl ‐deficient mice exhibit hepatomegaly and fasting hypoglycemia. Moreover, hepatic glycogen accumulation increases with age. Thus, Pygl ‐deficient mice at old age display excessive buildup of hepatic glycogen and at risk of liver damage, inflammation and fibrosis.